Analisis Sistematis Model dan Implementasi Teaching Factory Dalam Pendidikan Vokasi Serta Dampaknya Terhadap Kesiapan Kerja Siswa SMK - Adnyana, I Gusti Kadek Surya; Agustini, Ketut; Suartama, I Kadek (Cetta: Jurnal Ilmu Pendidikan, 2025)
Teaching Factory (TeFa) is an innovative approach in vocational education aimed at bridging the gap between the education sector and the industrial world. In the context of vocational high schools (SMK) in Indonesia, the implementation of TeFa is expected to enhance students' job readiness through real production-based learning. This study aims to systematically examine the models, implementation strategies, and the impact of TeFa on students' job readiness in Indonesian SMKs. The research employs a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. A total of 25 scientific articles published between 2017 and 2024 were analyzed using thematic analysis methods. The findings reveal that the dominant TeFa model used is the hybrid model, which integrates project-based learning with real production activities. However, most of these models have not been empirically tested against national competency standards. In terms of implementation, the main challenges include limited production facilities, lack of teacher training, and weak structural collaboration with industry. Evaluation of TeFa implementation is largely descriptive, using the CIPP model, with few studies employing quantitative or longitudinal indicators. The positive impacts of TeFa on students’ job readiness are mainly seen in soft skills development, motivation, and self-confidence, though these have not been systematically supported by alumni tracking data. This study concludes that while TeFa holds significant potential to strengthen the job readiness of vocational students, its implementation still faces structural and methodological challenges. Further research is needed, particularly using quantitative and longitudinal data, along with strengthened formal partnerships between vocational schools and industry to ensure the measurable and sustainable benefits of TeFa.